Understanding sustainability: an exploration of the is literature - Sutan Ahmad Nawi, Haslinda (Asian Research Publishing Network (ARPN), 2015)
Government all over the world are increasingly realizing that implementing and sustaining their electronic service delivery is the way forward to achieve efficiency savings and to satisfy and engage demanding constituents. Once an electronic service delivery has been developed and the infrastructure is in place, they are almost infinitely scalable with minimal effort, and will reduce variable costs of electronic service provisioning and service use. As this trend continues, academics, IT professionals and decision makers need a deeper understanding of electronic service initiatives sustainability. Yet, analysis of IS academic literature reveals that electronic service initiatives sustainability, has received little in depth attention. This paper investigates the current state of electronic service initiatives sustainability research in IS literature. The article detailed out a review of literature from main IS journals. The study concludes with a tentative operational definition, a list of source references, and an agenda for related future research.